Pengalaman Ibu dalam Merawat Bayi dengan Prematur dan Berat Badan Lahir Rendah: Mother's Experience in Caring for Premature Babies and Low birth weight - Deswita (Fakultas Keperawatan Universitas Andalas, 2013)
Taking care of the infants becomes a separate stressor especially if the infants is born with premature and infants who have low birth weight. Many problems arise, if the infants is not treated as it should lead to disability and even death. However, there are some mothers who successfully care for premature and low birth weight infants in the house. Mothers who successfully treat premature babies and low birth weight at home is a situation that is very interesting to learn, because with the new gain experience premature and low birth weight, the mother has been able to take good care. The purpose of this research is in the picture get it mother's experience in caring for premature and low birth weight infants in the house. This study used a qualitative research design with a phenomenological study. Participants of this study were mothers who have had premature and low birth weight infants in the treated at home part of Puskesmas Ambacang. Intake of participants conducted purposive sampling technique, with the number 5 . Themes were identified from the interview are as many as 5 ( five ). These themes are: (1) Characteristics of premature and low birth weight infants , ( 2 ) the mother 's response to premature birth and low birth weight ( 3 ) Treatment of premature and low birth weight infants in the house, ( 4 ) Support the mother in caring for premature and low birth weight infants,(5)Hope maternal health services.